Gastrointestinal stromal tumour of the rectum: a report of two cases - Chekrine, Tarik (The African Field Epidemiology Network, 2012)
Gastrointestinal stromal tumours (GISTs) are the most common mesenchymal tumours of the gastrointestinal tract in adults, although rectal localisation of these tumours is very rare. We report here two cases of rectal stromal tumours in a 77-year-old woman and a 65-year-old man, confirmed by histology and immunohistochemistry. Surgery for rectal GIST patients is the standard treatment and adjuvant imatinib, a tyrosine kinase inhibitor, is indicated for GISTs with a high risk of malignancy, as well as in the case of metastatic or unresectable tumours.